Dathlu! - Cadwaladr, Rhian (Gwasg Carreg Gwalch, 2022)
On the eve of their 60th birthdays, four lifelong friends venture on a special journey. As their lives have all been in complete contrast to one another, will the celebration turn bitter?. Intro – Clawr – Teitl – Hawlfraint – Cyflwyniad a diolchiadau – Prolog – Pennod 1 - Gwawr – Pennod 2 - Sioned – Pennod 3 - Linda – Pennod 4 - Iola – Pennod 5 – Pennod 6 – Pennod 7 – Pennod 8 – Pennod 9 – Pennod 10 – Pennod 11 – Pennod 12 – Pennod 13 – Pennod 14 – Pennod 15 – Pennod 16 – Pennod 17 – Pennod 18 – Pennod 19 – Pennod 20 – Epilog – Nofelau eraill gan Rhian Cadwaladr.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books